2014
DOI: 10.4314/tjpr.v13i9.15
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity, Radical Scavenging Kinetics and Phenolic Profile of Methanol Extracts of Wild Plants of Southern Sonora, Mexico

Abstract: Rhizophora mangle L (688.45 ± 18.21 and 7.13 ± 0.125 mg/g, respectively) and Krameria erecta (619.92 ± 28.16 mg/g and 22.29 ± 0.72 mg/g, respectively) than the other constituents. Conclusion: Rhizophora mangle and Krameria erecta possess five times the antioxidant activity of ascorbic acid and also demonstrate high phenolic contents, which supports the beneficial properties attributed to these plants in traditional medicine, and also justifies the use of the plants as alternative medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…The most abundant compounds in the genus Rhizophora are polyphenolic compounds, such as proanthocyanidins (PAs), consisting of oligomers and polymers with flavan-3-ol units . The compounds mentioned are secondary metabolites generated from the plant’s defense reaction against environmental aggressions (variations in water temperature, tides, climate, pollution, and microorganisms). , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most abundant compounds in the genus Rhizophora are polyphenolic compounds, such as proanthocyanidins (PAs), consisting of oligomers and polymers with flavan-3-ol units . The compounds mentioned are secondary metabolites generated from the plant’s defense reaction against environmental aggressions (variations in water temperature, tides, climate, pollution, and microorganisms). , …”
Section: Resultsmentioning
confidence: 99%
“…These compounds expressed efficient antioxidant capacity, and as already suggested, some are possible antioxidants present in the chemical composition of R. mangle. [5][6][7][8][9][10][11]38,39,41 The groups highlighted that the positive points of the CRAC assay compared to the FRAP assay are the simplicity because it does not require the preparation of many solutions, the use of an oxidizing species of great stability, and low cost. Some errors were also observed in the FRAP assay, such as inaccuracy in the reaction time, difficulty in reading the absorbance in dark or cloudy solutions, and the influence of solvent systems.…”
Section: Crac Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Alam et al (2017) reported that amino acids maintain nutrients balance in maize hybrids under salt stress. Some amino acids such as serine, glycine, valine and glutamate play role in improving plant health through therapeutic elements (Moran-Palacio et al, 2014). Proline and glycinebetaine (GB) improve crop production by reducing oxidative stress (Ashraf and Foolad, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Lycium berlandieri es una planta que florece en el Desierto Chihuahuense y Sonorense, que posee bayas rojas, jugosas, sabor agridulce y ligeramente amargas, consumidas por los nativos americanos (Matthews, 1994). En la actualidad se utiliza en la medicina tradicional del estado de Sonora, ya que posee actividad antifúngica contra Aspergillus niger y Aspergillus flavus, así como actividad antibacterial contra Staphylococcus aureus y Streptococcus phyogenes (Moran et al, 2014). Está f ilogenéticamente relacionada con la especie Lycium barbarum, una planta de la medicina tradicional china, que, por su amplio uso para inhibir la proliferación de células cancerígenas, incrementar la respuesta del sistema inmunológico y prevenir la degeneración macular asociada a la edad (Inbaraj et al, 2010), en los últimos años ha tenido importancia comercial.…”
Section: Introductionunclassified